Effect of bioactive glass-containing resin composite on dentin remineralization. (August 2018) - Jang, Ji-Hyun; Lee, Myoung Geun; Ferracane, Jack L.; Davis, Harry; Bae, Han Eul; Choi, Dongseok; Kim, Duck-Su
Abstract: Objectives: The purpose of this study was to evaluate the effect of bioactive glass (BAG)-containing composite on dentin remineralization. Methods: Sixty-six dentin disks with 3 mm thickness were prepared from thirty-three bovine incisors. The following six experimental groups were prepared according to type of composite (control and experimental) and storage solutions (simulated body fluid [SBF] and phosphate-buffered saline [PBS]): 1 (undemineralized); 2 (demineralized); 3 (demineralized with control composite in SBF); 4 (demineralized with control composite in PBS); 5 (demineralized with experimental composite in SBF); and 6 (demineralized with experimental composite in PBS). BAG65S (65% Si, 31% Ca, and 4% P) was prepared via the sol-gel method. The control composite was made with a 50:50 Bis-GMA:TEGDMA resin matrix, 57 wt% strontium glass, and 15 wt% aerosol silica. The experimental composite had the same resin and filler, but with 15 wt% BAG65S replacing the aerosol silica. For groups 3–6, composite disks (20 × 10 × 2 mm) were prepared and approximated to the dentin disks and stored in PBS or SBF for 2 weeks. Micro-hardness test, attenuated total reflection Fourier-transform infrared spectroscopy (ATR-FTIR) and field-emission scanning electron microscopy (FE-SEM) was investigated. Results: The BAG-containing composite significantly increased the micro-hardness of the adjacent demineralized dentin. ATR-FTIR revealed calcium phosphate peaks on the surface of the groups which used BAG-containing composite. FE-SEM revealed surface deposits partially occluding the dentin surface. No significant difference was found between SBF and PBS storage. Clinical Significance: Bioactive glass is a potentially useful material for remineralization of tooth structure. When incorporated into a resin composite, it may aid in remineralizing the adjacent demineralized dentin, thus preventing further destruction of the tooth. Conclusion: BAG-containing composites placed in close proximity can partially remineralize adjacent demineralized dentin.